Nonlinear optical studies of calcium tartrate crystals. Issue 1 (11th December 2019) - Rejeena, I.; Thomas, Vinoy; Mathew, S.; Elizabeth, Anit; Radhakrishnan, P.; Mujeeb, A.
Abstract: Calcium Tartrate crystals were synthesized using sol–gel technique. Linear optical studies of the crystals were carried out in the UV–Vis-NIR spectral range. Nonlinear optical open aperture z-scan studies were done using high sensitive z-scan experimental technique. Both saturable absorption and reverse saturable absorption behaviour were observed at different input fluences. Reverse saturable absorption characteristic of the crystals make them suitable for optical limiting applications. Our analysis revealed that the novel crystal has the optimum values for the optical limiting parameters which are required for a high-performance optical limiter.